Research progress of flexible wearable pressure sensors - Wang, Xiangfu; Yu, Jihong; Cui, Yixuan; Li, Wei (Sensors and actuators. A. Physical., 2021)
[Display omitted] Flexible pressure sensors with high sensitivity, high flexibility, lightness and easy integration have been extensively researched in the fields of electronic skin, wearable devices, medical diagnosis, physical health detection and artificial intelligence. This review summarizes the latest research progress of piezoresistive pressure sensors, capacitive pressure sensors, and piezoelectric pressure sensors. In addition, high-performance flexible pressure sensors designed for different application requirements such as self-powered pressure sensors, multifunctional pressure sensors, and self-healing pressure sensors are also discussed. After a comprehensive description of the latest flexible pressure sensors, we discussed the current challenges and potential prospects of flexible pressure sensors. Exploring new sensing mechanisms, seeking new functional materials, and developing novel integrated technologies for flexible devices will be the key direction in the sensor field in the future.